MANIFESTATIONS OF SERVICE CULTURE AMONG STREET VENDORS IN BOTSWANA - Byron Brown; Goaletsa Rammidi (European Scientific Journal, ESJ, 2014)
In the non-western developing world, where the majority of the world’s street vendors can be found, service culture is under-researched. For instance, although street vendors are entrepreneurers, it is not always clear how or to what extent they value customers. Nor is it self-evident what kinds of service culture prevail in street vendors’ business, or how such culture supports service improvement. Using a qualitative approach, involving a sample of 30 street vendors who were interviewed and observed, this research describedthe basic characteristics of the service culture practices and values among street vendors in microenterprises. The study found that unique service cultures prevail among street vendors, ranging from humane clues evidenced in practices and values in encounters with customers and interaction with each other, to mechanic clues evidenced in the orchestration of their physical environment. A major contribution of this study is in showing that understanding the characteristics of the service culture in terms of practices and values provides useful insights for service quality improvement in street vending. The study made various recommendations for informal sector development.